Bentuk-Bentuk Etika Bermedia Sosial Generasi Milenial - Sri Hapsari Wijayanti; Kasdin Sihotang; Vanessa Emmily Dirgantara; Maytriyanti (Program Studi Ilmu Komunikasi, 2022)
This study aims to reveal and identify forms of social media etiquette for the millennial generation in Jakarta. Participants of this study were 268 students at a private university in Jakarta. The social media observed were Facebook, Instagram, WhatsApp, and Line. From the results of distributing online questionnaires, online interviews, documentation, and observations in the lecture and student organizations, it was found that the language used on social media between lecturers and students was formal and informal Indonesian. The language used on social media between students and peers is Indonesian and English, mixed with alay (slang). Social media etiquette includes not offending others, rereading messages before being sent, choosing the right time, choosing polite words for permitting, saying greetings, saying thanks, introducing him/herself, and not interrupting the talk. Nevertheless, etiquette violations are found in using impolite or sarcastic words.